Characteristics, Curve and Persistency of Lactation in Jaffarabadi (Bubalus bubalis) Buffaloes - Chaudhari, Pravin N.; Kapadiya, Pratik S.; Gadariya , Mahesh R. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Lactation milk yield in dairy bovines is closely related with, and therefore a function of, peak yield, persistency and lactation length.  Therefore, characteristics, curve, and persistency of lactation were studied in Jaffarabadi (Bubalus bubalis) buffaloes. A total of 1,15,339  daily morning and evening milk production performance records in 176 lactations of 1st to 6th parity of 30 Jaffarabadi buffaloes lactating  at the Cattle Breeding Farm, JAU, Junagadh, Gujarat over a period of 28 years (1991-2018) were used for the study. Overall lactation length  (LL), total lactation milk yield (TLMY), and standard lactation milk yield (SLMY) of the Jaffarabadi buffalo averaged 325.90 ± 5.53 days,  2009.31 ± 42.13 lit and 1872.61 ± 32.88 lit, respectively. Overall daily peak yield (DPY) was 11.27 ± 0.20 lit/day, attained at 102.00 ± 4.68  days postpartum. Overall weekly peak yield (WPY) and weeks to attain WPY averaged 64.79 ± 1.09 lit/week and 13.72 ± 0.64 weeks,  respectively. Weekly milk yield could be predicted using linear function [(ŷ = 59.149 + (–0.6634) × X)] and logarithmic function  [(ŷ = 1.80 × (–0.0008)^X)] with an accuracy of 66 to 73%. In contrast, monthly milk yield could be predicted using linear function [(ŷ =  261.64 + (–13.229) × X)] and logarithmic function [(ŷ = 2.45 × (–0.035)^X)] with comparatively more precision, R2 value being 79.7 to  81.2 %. Overall persistency in terms of weekly and monthly milk yield was estimated to be 98.03±0.24% and 91.24±0.59%, respectively.
Keywords: Characteristics; Jaffarabadi (Bubalus bubalis) buffalo; Lactation curve; Linear regression; Peak yield; Persistency